An analysis Franza Lisz's stylistic development as manifested by the three compositional stages of the12 etudes, op.1 (1826), the douze grandes etudes (1838) and the final version, etudes d'execution transcendante (1851). - Cilliers, D (College of Music, 2024)
Individual etudes need to be related to their reworked and/or revised counterparts in the other sets, and on the other hand, comparisons also have to be drawn between general stylistic aspects as they are contained within each individual set. In addition, whole sets require stylistic comparison with one another. A total of 37 pieces are involved, all of which share various degrees of similarity in style and content. The first chapter deals with style so that it traces general procedures in the various compositional stages under the separate headings of rhythm, melody, harmony, etc. Examples are included in order to support findings. To compensate for a measure of detail lost in this process, the second chapter offers a detailed description of the evolution undergone towards the final versions of two etudes. The fact that no gradual chronological evolution had taken place among the various versions of the pieces, posed a difficulty to organisation. The second and third sets are more closely related to each other than the first and second sets. The second set contains new compositions loosely related to the first set, and the third set represents a revision of the second. In addition, the second version never constitutes the final masterpieces and it is at best regarded as an initial manifestation of the final concept. Other than providing the key scheme and basic thematic ideas, the first set does not have much bearing on the later sets. As a result, only two main sets emerge, the second comprising the later two versions. It is because of all these factors that the order of discussion in the second chapter may appear strange at first.